Guide to improved pastures for the drier areas of the Eastern Caribbean - Paterson, R.T. (CARDI St John'sAT, 1986)
Recommends pasture species (grasses and legumes) suitable for farms situated on neutral to calcareous soils in the drier areas of the Eastern Caribbean. Suggests alternative feeds for livestock. Gives guidelines for the establishment and maintenance of pastures and also for grazing. Suggests strategies for greater farm profit.